1994
DOI: 10.1557/proc-339-267
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Chemical Vapor Deposition: Gas Compositions and film Properties

Abstract: Rate, crystallinity and phase purity of vapor-grown diamond deposits are discussed. Emphasis is on microwave plasma CVD of diamond from C/H-, C/H/O-, C/H/F-, C/H/CI- and C/H/N-gas mixtures.The manufacture of wear-resistant diamond thin films, diamond vacuum window membranes and thick diamond heat spreader plates are used as examples to outline the influence of various deposition parameters on the performance of finished products and to describe the use of ternary gas phase compositional diagrams as tools for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Our chlorine assisted diamond growth studies shows that if the Cl input fraction is too high (Ͼ0.06͒ the quality of the diamond grown at normal substrate temperatures (ϳ900°C͒ is reduced, probably because a large fraction of surface sites are activated, leading to the graphitization of the diamond surface. These findings broadly agree with the diamond growth domain indicated in the C/H/Cl ternary gas-phase composition diagram of Bachmann et al 37 However, at lower substrate temperatures the presence of such chlorine concentrations in the process gas mixture would result in an increased deposition rate due to the greater efficiency of surface hydrogen abstraction by Cl atoms.…”
Section: Discussionsupporting
confidence: 90%
“…Our chlorine assisted diamond growth studies shows that if the Cl input fraction is too high (Ͼ0.06͒ the quality of the diamond grown at normal substrate temperatures (ϳ900°C͒ is reduced, probably because a large fraction of surface sites are activated, leading to the graphitization of the diamond surface. These findings broadly agree with the diamond growth domain indicated in the C/H/Cl ternary gas-phase composition diagram of Bachmann et al 37 However, at lower substrate temperatures the presence of such chlorine concentrations in the process gas mixture would result in an increased deposition rate due to the greater efficiency of surface hydrogen abstraction by Cl atoms.…”
Section: Discussionsupporting
confidence: 90%
“…But over the past 10 years, there have been a large number of studies of the gas phase chemistry (Goodwin & Butler 1997), and we are now beginning to obtain a clearer picture of the important principles involved. The first clue was obtained from the 'Bachmann triangle diagram' (Bachmann et al 1994), which is a C-H-O composition diagram based upon over 70 deposition experiments in different reactors and using different process gases (see figure 3). Bachmann found that independent of deposition system or gas mixture, diamond would only grow when the gas composition was close to and just above the CO tie-line.…”
Section: The Chemistry Of Cvd Diamond Growthmentioning
confidence: 99%
“…Low-pressure diamond deposition has been achieved using a large range of C, H, and O containing gas mixtures. Bachmann et al 1,2 summarized the results of many deposition experiments involving various gas mixtures and reactor types in the form of an atomic C-H-O phase diagram. They concluded that the exact nature of the source gases was unimportant for most diamond chemical vapor deposition ͑CVD͒ processes and that, at typical process temperatures and pressures, it was only the relative ratios of C, H, and O that controlled deposition.…”
Section: Introductionmentioning
confidence: 99%